Power, precision, and sample size estimation in sport and exercise science research - Abt, G.; Boreham, C.; Davison, G.; Jackson, R.; Nevill, A.; Wallace, E.; Williams, M. (Journal of Sports Sciences, 2020)
To get a sense of the sample sizes and methods used to estimate sample size by studies submitted to the Journal of Sports Sciences we randomly selected 120 papers submitted over the previous three years. The data were positively skewed, so the median (median absolute deviation) sample size was 19 (11). Of these 120 papers only 12 included a formal a priori sample size estimation based on power and 1 estimated sample size using a precision approach. Although the 12 papers that did include an a priori power calculation identified the effect size to be detected, alpha, and power, all of those papers failed to include full information on the statistical test(s) to be conducted to detect the chosen effect size and 4 failed to include a convincing rationale for why the given effect size was chosen.